Co-Partisan Buddies or Partisan Bullies? Why State Supervision of Local Government Borrowing Fails - Felix Rösel (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2014)
In many federal countries, local governments run large deficits, even when supervision by state authorities is tight. I investigate whether party alignment of mayors and supervisors influences local government borrowing. The dataset includes 427 local German governments over the period 19992012. I exploit variation of a far-reaching institutional reform that entirely re-distributed political powers on both debt issuance and supervision. The results show that short-term deficits of local governments are not enabled by a vertical buddy relationship between a mayor and a supervisor affiliated with the same party (co-partisanship) but rather by an ideological bully behavior of partisan supervisors and supervisees: left-wing local governments issue more debt, while left-wing supervisory authorities tolerate more debt. These findings imply that political independence for state supervisory authorities is highly recommended.
Keywords: H62; H74; H77; 330; Local government; public deficits; supervision; partisan cycle